Peningkatan Kompetensi Pengurus Koperasi Kelurahan Merah Putih Melalui Pelatihan Inovasi Digital di Kota Blitar - Eddy Refianto (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2026)
Rural economic development in Indonesia faces the challenge of the digital divide, especially in cooperative governance. This study aims to evaluate the effectiveness of the digitalization training for the management of Village Cooperatives/Merah Putih Villages in Blitar City in order to support Presidential Instruction No. 9 of 2025. Using the One-Group Pretest-Posttest design, the training involved 42 cooperative administrators selected through purposive sampling. The intervention was carried out using the Participatory Action Learning (PAL) method which integrates the simulation of the Simkopdes application and the LMS Talentakoperasi.id. Effectiveness was measured using 15 indicators of technical competence. The results showed a significant increase in the average competency score from 50.43 (pre-test) to 92.47 (post-test) with a significance value of p=0.000. The N-Gain test showed a score of 0.85 (High Category), indicating strong intervention effectiveness. Specific findings show that the Point of Sales (POS) feature has the highest adoption rate, while the Login by WhatsApp feature on the LMS has proven to be effective in overcoming technological barriers in elderly participants. The study concludes that the digital transformation of village cooperatives can be accelerated through a participatory training approach and the use of user-friendly technology.